2004
DOI: 10.1038/sj.bjc.6601655
|View full text |Cite
|
Sign up to set email alerts
|

Patient's needs and preferences in routine follow-up after treatment for breast cancer

Abstract: The purpose of the study was to analyse the needs of women who participated in a routine follow-up programme after treatment for primary breast cancer. A cross-sectional survey was conducted using a postal questionnaire among women without any sign of relapse during the routine follow-up period. The questionnaire was sent 2 -4 years after primary surgical treatment. Most important to patients was information on long-term effects of treatment and prognosis, discussion of prevention of breast cancer and heredita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
3
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 32 publications
12
84
3
7
Order By: Relevance
“…In a previous publication, patients in group A preferred multiple follow-up visits per year after a median follow-up of three years 2 . This is comparable to the preference of group B in this study with a similar follow-up duration; almost 75% of these patients preferred visits more frequently than M A N U S C R I P T…”
Section: Needs and Preferences; Frequency And Duration And Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous publication, patients in group A preferred multiple follow-up visits per year after a median follow-up of three years 2 . This is comparable to the preference of group B in this study with a similar follow-up duration; almost 75% of these patients preferred visits more frequently than M A N U S C R I P T…”
Section: Needs and Preferences; Frequency And Duration And Professionmentioning
confidence: 99%
“…The first group, group A, consisted of patients operated before the introduction of the breast cancer unit (1998-1999, n=89) and had previously participated in a patient satisfaction survey in 2004 2 . These patients were only incidentally seen by a nurse practitioner.…”
Section: Patientsmentioning
confidence: 99%
“…A survey carried out in 2001 in the Netherlands among women 2-4 years post treatment for ebc reported that more than half the patients preferred lifetime follow-up twice annually, and 86% preferred follow-up by a hospitalbased physician 33 . Similarly, among 285 women with ebc in the United Kingdom, 85% preferred regular follow-up in a breast clinic, and 76% preferred regular breast clinic visits rather than family physician follow-up 34 .…”
Section: Attitudes Of Primary Care Physicians Oncologists and Patiementioning
confidence: 99%
“…Several studies have highlighted that high levels of distress in the transition period can result in poorer long-term adjustment (Cimprich et al, 2005;Allen et al, 2009 information needs are associated with higher anxiety and depression (De Bock et al, 2004) and ongoing physical and psychological symptoms can lead to poorer quality of life (Cappiello et al, 2007). Given the current changes taking place in cancer care, coupled with an identified need both for tools for cancer survivors and the lack of research to inform what is needed at this time, it is timely to conduct this research to ask what cancer survivors want from a resource at the end of their active treatment and transition to ongoing survivorship.…”
Section: Introductionmentioning
confidence: 99%